Penerapan Model Pembelajaran Kooperatif Tipe Quick On The Draw Untuk Meningkatkan Aktivitas Dan Hasil Belajar PKn pada materi hubungan gambar pada lambang negara dengan sila-sila pancasila kelas II MIN 8 Aceh Barat Daya - Suwirda, Erma (Universitas Serambi Mekkah, 2020)
The Application of the Cooperative Learning Model Type Quick On The Draw to Increase Civics Ac-tivity and Learning Outcomes in the Material Relationship Pictures on the National Symbols with the Principles of Pancasila Class II MIN 8 Southwest Aceh Aceh 2019/2020 Academic Year